Geological Methods in Mineral Exploration and Mining - Marjoribanks, Roger; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
This practical step-by-step guide describes the key geological field techniques needed by today's exploration geologists involved in the search for metallic deposits. The techniques described are fundamental to the collection, storage and presentation of geological data and their use to locate ore. This book explains the various tasks which the exploration geologist is asked to perform in the sequence in which they might be employed in an actual exploration project. Hints and tips are give. The steps are illustrated with numerous examples drawn from real projects on which the author has worked. The book emphasizes traditional skills and shows how they can be combined effectively with modern technological approaches.
Prospecting and the Exploration Process -- Geological Mapping in Exploration -- Mine Mapping -- Trenching and Underground Development -- Drilling: A General Discussion the Importance of Drilling -- drilling, rotary percussion bits Rotary Percussion and Auger Drilling -- Diamond Drilling -- satellite images Satellite Imagery -- Geophysical and Geochemical Methods -- GIS Geographical Information Systems and exploration data bases Exploration Databases.
Keywords: Geography; Geology, economic; Mines and mineral resources; Environmental management; Earth Sciences; Economic Geology; Mineral Resources; Geotechnical Engineering & Applied Earth Sciences; Environmental Management; Fossil Fuels (incl. Carbon Capture).